Special conditions in the treatment of hemorrhoidal disease. The advantages of THD-RAR in the treatment of hemorrhoidal disease in these situations - Romica Mehic; Veronica Indreica; Vasilica Marcu; Mircea Beuran; Alexandru Laurentiu Chiotoroiu (Romanian Medical Journal, 2020)
Introduction. The prevalence of hemorrhoids in the general population ranks first among benign anorectal diseases. In the last 20 years, however, the number of cases operated for hemorrhoidal disease has decreased and consequently the experience of surgeons in treating this condition has diminished and even less those cases associated with other complex pathologies that sometimes pose special treatment problems. Material and methods. We have studied the articles published in the period 1990-2020, which referred to special condition in patients with hemorrhoidal disease (young, elderly, pregnant woman, coagulation disorders, immunosuppressive states, colon inflammatory diseases, cirrhosis, renal failure, neurological diseases, associated perianal diseases). The recommendations we made were based on summing and updating the data found, conducting a critical review of the results of these studies, to which was added our personal experience, making special reference to the transanal hemorrhoidal dearterialisation (THD) technique. Conclusions. The physiological features of the various stages of human evolution as well as the association with hemorrhoidal disease of other diseases that influence their symptoms and evolution require understanding in their close interdependence. Although hemorrhoidal disease is not a severe condition, it can affect the patient's social life or it can lead to unwanted complications or reinterventions if the therapeutic attitude is not adapted to the patient's associated conditions. The minimal damage of the anal anatomical structures in the THD technique makes the postoperative risks to be minimal even if a series of additional factors specific to the disease associated with hemorrhoids overlap. This makes THD a feasible therapeutic option for these at-risk patients.